Tunneling Pipe Mode Pada Jaringan Multi Protocol Label Switching - ade Nurhayati (PPM Telkom University, 2020)
Along with the developing and the increasing of data communication users, service providers are required to always improve the quality of their services. QoS plays an important role since it is a parameter of the quality level of a service. Pipe Tunneling technique is one of the Qos methods that will guarantee a service will have its own priority level. With the help of the MPLS-VPN protocol, addressing of the IP will be much more flexible. In this thesis the simulation was done using GNS3 software while the results of the analysis were carried out using the WireShark software. There are two scenarios done by the author. For MPLS-VPN the author simulates 2 customers between companies 1 and 2 where both companies have centers in Jakarta and branches in Surabaya. And for Tunneling, both companies want their services to be given the highest priority among other services. From this scenario it can be obtained that with the presence of VRF on the network if there is the same network usage there will be no overlaps of IP. A service will have its own priority level according to the needs and requests. The results of the analysis are more focused on QoS, especially delay and throughput. From the results it shows that MPLS-VPN with Tunneling Pipe Mode integration is able to keep good QoS value. This can be seen from the average of the delay and throughput yield for Tunneling Pipe Mode that is equal to 84,51 ms and 67,858 Bytes / s.